Review of the symposium «Recommendations for the treatment of patients with frequent combination of gastrointestinal symptoms» - I. V. Kovaleva (Лечащий Врач, 2021)
The article provides an overview of the reports of the satellite symposium «Recommendations for the treatment of patients with frequent combination of gastrointestinal symptoms», which took place within the framework of the 116th International Session of the National School of Gastroenterology and Hepatology of the Russian Gastroenterological Association. The speakers discussed the approaches to the management of patients with a typical, frequent combination of gastrointestinal symptoms using specific examples from their clinical practice. Special emphasis in the reports was made on the role of microbiota in maintaining and strengthening the physical and mental health of a person, the negative consequences of dysbiotic changes in the gastrointestinal tract and the use of pro- and prebiotics to correct these changes.